Venetoclax-Related Neutropenia in Leukemic Patients: A Comprehensive Review of the Underlying Causes, Risk Factors, and Management - Laura Giuseppina Di Pasqua; Murwan Mahmoud Abdallah; Fausto Feletti; Mariapia Vairetti; Andrea Ferrigno (MDPI AG, 2024)
Venetoclax is a Bcl-2 homology domain 3 (BH3) mimetic currently approved for the treatment of chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) that has proven to be highly effective in reinstating apoptosis in leukemic cells through the highly selective inhibition of the anti-apoptotic protein B-cell lymphoma-2 (Bcl-2). Clinically, venetoclax has provided lasting remissions through the inhibition of CLL and AML blasts. However, this activity has often come at the cost of grade III/IV neutropenia due to hematopoietic cells' dependence on Bcl-2 for survival. As life-threatening infections are an important complication in these patients, an effective management of neutropenia is indispensable to maximize patient outcomes. While there is general consensus over dose reduction and scheduling modifications to minimize the risk of neutropenia, the impact of these modifications on survival is uncertain. Moreover, guidelines do not yet adequately account for patient-specific and disease-specific risk factors that may predict toxicity, or the role combination treatment plays in exacerbating neutropenia. The objective of this review is to discuss the venetoclax-induced mechanism of hematological toxicity, the potential predictive risk factors that affect patient vulnerability to neutropenia, and the current consensus on practices for management of neutropenia.